Sistem Pendukung Keputusan Pemberian Peringkat SMA Pada Dinas Pendidikan Menerapkan Metode PROMETHEE II dan Pembobotan Menggunakan AHP - Ari Andini (Journal of Computer System and Informatics (JoSYC), 2021)
School ranking is a comprehensive and comprehensive school assessment (assessment) activity through office evaluations and external evaluations (visits) to determine school eligibility and performance. In the assessment of high schools, which are currently not objective because the Dinas is still conducting direct surveillance to school without taking supporting data in providing ratings. Because it does not yet have a good system, so that there are conflicts that arise in the provision of ratings. Therefore using a decision support system based on Promethee II and weighting using AHP. It is hoped that decision makers will be helped and reduce the conflict that exists in granting high school rankings to the Education Office.